Familiarity plays a small role in noun comprehension at 12–18 months. (15th April 2020) - Garrison, Hallie; Baudet, Gladys; Breitfeld, Elise; Aberman, Alexis; Bergelson, Elika
Abstract: Infants amass thousands of hours of experience with particular items, each of which is representative of a broader category that often shares perceptual features. Robust word comprehension requires generalizing known labels to new category members. While young infants have been found to look at common nouns when they are named aloud, the role of item familiarity has not been well examined. This study compares 12‐ to 18‐month‐olds' word comprehension in the context of pairs of their own items (e.g., photographs of their own shoe and ball) versus new tokens from the same category (e.g., a new shoe and ball). Our results replicate previous work showing that noun comprehension improves rapidly over the second year, while also suggesting that item familiarity appears to play a far smaller role in comprehension in this age range. This in turn suggests that even before age 2, ready generalization beyond particular experiences is an intrinsic component of lexical development.